Diversification of Nigeria Economy and National Development 2005-2012 - Sunday Mba, Ibiam; Eme; Innocent, Okechukwu; Obinnaiheji, Ihejirika Ngozi (Journal of Public Administration and Governance, 2023)
Economic diversification has been the only solution to Nigeria’s economic challenges with the country in control of diversely untapped natural and human resources. This work has contextually x-rayed some much more considered theoretical paths of economic development through economic diversification and placed the blame for Nigeria’s economic backwardness on political will and lack of commitment to national course of political leaders. Since the diverse policy process of the government had yielded little or no sustainable results, even when the emphasis is to utilize the potentials in non-oil sectors to benefit ever-increasing population. Nigeria is relatively diversified but the positive impact of real diversification through surplus economic gains has not been achieved. A holistic approach to development was adopted in the theoretical framework used in this work that positively affects state, people and their relationship nationally and internationally. The thrust of the theory encourages free trade policy, efficient competition and democratic features to liberalize productivity through various guided legislation in line with Globalized Quality Standard. The research design was descriptive of the observed trend in the economy. It also analyses similar scholarly data collected for accuracy in exposing greatly a multi-sectoral approach in planning, dealing with interdependence using input-output matrix with reference to pre-independence and post-independence era of the national economy. This study looked at the positive intentions of some interventionist programmes and policies of the Government which were short-lived. Few years’ aggregate contribution and sectoral real GDP rate were stated. Recommendations were effectively based on keen interest in multi-sectoral diversification of an economy being the sub-structure that determines the effectiveness of super-structure.